Keşif Defteri Işığında ErzincanRefahiye/Yazıgediği Köyü’nde Bulunan Bahriye Nazırı Hasan Hüsnü Paşa Camisi. - NALDAN, Funda; SEÇKİN, Selçuk (Erdem, 2022)
The mosque is located in the village Yazıgediği depending on the county Erzincan’s Refahiye. According to the construction inscription on the entrance gate, it was built in 1893 by the Minister of the Navy Hasan Hüsnü Pasha. Before 1891, the project fort he construction of the mosque was prepared by the Minister of the Navy[1] Hasan Hüsnü Pasha, but it was reported by the Ministry of Naval Affairs in 1891 that there were no necessary tools and equipment. Later, the mosque was completed in 1893 due to a need in this village. The mosque has a rectangular plan and is covered with a flat wooden ceiling. It is covered with a hipped roof from the outside. The top cover is supported by 16 wooden legs. The pillows on wooden legs in the middle section have a medallion-like decoration made with wood carving technique. The entrance hall was added to the northern part of the mosque which does not have a final congregation place. Since the mosque is plastered with concrete mortar the masonry is not visible. However, as can be seen from the plaster traces and spills on the body walls, it was covered with cut stone material. Cut stone material was also used in the sanctuary door and window jambs. The inverted “U” shaped mihrab in the South was later painted with oil paint. The pulpit is a new element added later. The women’s hall which can be climbed from the west direction in the north extends in the east-west direction. The plan and architectural features of the mosque are in parallel with the mosque architecture in Erzincan. These mosques built in the Ottoman Period have a small size simple and simple architecture. In this study, the documents in the Prime Ministry Ottoman Archive were evaluated and the current situation, plan and architectural features of the building were evaluated. The construction process of the building and its inscription are examined under separate headings. Information such as plan and section in the Project included in the exploration book has been included in the study and its similar and different features with the existing mosque are diccussed. The absence of the narthex and the coffin section the location of the wooden minaret the differences in the number of Windows and wooden carriers are remarkable. Refahiye in Erzincan province is on the Erzincan-Sivas highway. Until 1872, Refahiye was called “Gercanis” in the Ottoman administrative division. Gercanis was formerly a sub-district of Kemah, later it was connected to the Erzincan Sanjak and has come to this day as the center of the Refahiye district. It is not known when the village was established. The name of the village is mentioned as “Pusans”, “Posans” in the records. The village is far 25 km. from district center Refahiye. The mosque, which is open to worship today, has been left quite neglected and needs to be restored. The mosque should be protected and its originality should be preserved by removing the additions that do not conform to its architecture.